Kinsenoside Protects Against Radiation-Induced Liver Fibrosis via Downregulating Connective Tissue Growth Factor Through TGF-β1 Signaling - Nie, Xiaoqi; Yu, Qianqian; Li, Long; Yi, Minxiao; Wu, Bili; Huang, Yongbiao; Zhang, Yonghui; Han, Hu; Yuan, Xianglin (Frontiers in Pharmacology, 2022)
Radiation-induced liver fibrosis (RILF) is a serious complication of the radiotherapy of liver cancer, which lacks effective prevention and treatment measures. Kinsenoside (KD) is a monomeric glycoside isolated from Anoectochilus roxburghii, which has been reported to show protective effect on the early progression of liver fibrosis. However, the role of KD in affecting RILF remains unknown. Here, we found that KD alleviated RILF via downregulating connective tissue growth factor (CTGF) through TGF-β1 signaling. Sprague-Dawley rats were administered with 20mg/kg KD per day for eight weeks after a single 30Gy irradiation on the right part of liver, and tumor-bearing nude mice were administered with 30mg/kg KD per day after a single fraction of 10Gy on the tumor inoculation site. Twenty-four weeks postirradiation, we found that the administration of KD after irradiation resulted in decreased expression of α-SMA and fibronectin in the liver tissue while had no adverse effect on the tumor radiotherapy. Besides, KD inhibited the activation of hepatic stellate cells (HSCs) postirradiation via targeting CTGF as indicated by the transcriptome sequencing. Results of the pathway enrichment and immunohistochemistry suggested that KD reduced the expression of TGF-β1 protein after radiotherapy, and exogenous TGF-β1 induced HSCs to produce α-SMA and other fibrosis-related proteins. The content of activated TGF-β1 in the supernatant decreased after treatment with KD. In addition, KD inhibited the expression of the fibrosis-related proteins by regulating the TGF-β1/Smad/CTGF pathway, resulting in the intervention of liver fibrosis. In conclusion, this study revealed that KD alleviated RILF through the regulation of TGFβ1/Smad/CTGF pathway with no side effects on the tumor therapy. KD, in combination with blocking the TGF-β1 pathway and CTGF molecule or not, may become the innovative and effective treatment for RILF.